Sum-of-products form of the molecular electronic Hamiltonian and application within the MCTDH method - Sasmal, Sudip; Vendrell, Oriol (The journal of chemical physics, 2022)
We introduce two different approaches to represent the second-quantized electronic Hamiltonian in a sum-of-products form. These procedures aim at mitigating the quartic scaling of the number of terms in the Hamiltonian with respect to the number of spin orbitals and thus enable applications to larger molecular systems. Here, we describe the application of these approaches within the multi-configuration time-dependent Hartree framework. This approach is applied to the calculation of eigenenergies of LiH and electronic ionization spectrum of H2O.
Gesehen am 21.12.2022